انتقائية شباك الشنشيلا (الإحاطة Purse Seiene) والشباك المبطنة (المحير Trammel Net) لأنواع الأسماك المصطادة وأحجامها في المياه البحرية لمحافظة اللاذقية - إبراهيم أمير; حسن محمد; متوج أمجد (Latakia University Journal -Biological Sciences Series, 2019)
تعد الانتقائية التي تعبر عن قدرة الشباك على صيد أنواع أو أحجام معينة من التجمعات السمكية، إحدى الصفات المهمة لشباك الصيد. نفذت هذه الدراسة في ثلاثة موانئ صيد بحرية (الأزهري، برج إسلام، جبلة) وركزت على دراسة انتقائية نوعين من أنواع شباك الصيد الرئيسة وهي شباك الشنشيلا Purse Seiene والشباك المبطنة Trammel Net لأنواع الأسماك المصطادة وأحجامها في المياه البحرية السورية، بهدف الإسهام في وضع الحلول لمشكلة تدهور حجم المخزون السمكي. بينت نتائج البحث الحالي أن أقطار فتحات شباك الشنشيلا والشباك المبطنة المستخدمة في صيد الأسماك في المياه البحرية لمحافظة اللاذقية، كانت أصغر مما هو وارد في القرارات الناظمة لعملية الصيد بهذه الشباك، ما يعني خسارة اقتصادية وبيئية كبيرة للمخزونات الحية لهذه الأسماك. كما تبين أن شباك الشنشيلا كانت أكثر انتقائية من الشباك المبطنة نظراً لصيدها أنواعاً سمكية محددة كالأنواع التي تنجذب للضوء، في حين تم اصطياد طيف واسع من الأسماك بأنواع وأحجام مختلفة بوساطة الشباك المبطنة. لذا يجب إعادة النظر في فترات منع الصيد واستخدام طرائق الصيد ودراسة كل نوع من أنواع الشباك على حدة. Selectivity is one of the most prominent properties of a fishing gear. It describes its ability to catch exclusively restricted sizes or species from an existing fish community. This study was carried out in three fishing ports (Azhari, Jableh and Berj Islam), and it focused on the study of selectivity of two types of fishing nets: purse seine and trammel nets to fish species and sizes in the Syrian marine waters, in order to contribute to the development of solutions to the problem of the deterioration of the size of fish stocks. The results ofthis current research showed that the diameters mesh purse seine and trammel nets used in fishing in the marine waters of Lattakia were smaller than what is contained in the decisions governing of the operation of fishing using these nets, which means that there is a great economical and environmental loss of the large living stocks of these fish. It also indicated that the purse seine were more selective of the trammel nets and that because it caught specific fish species such as the specific types that are attracted to light, while a wide range of fish of different species and sizes were caught by using trammel nets. Thus, there should be a kind of reconsideration in the prevention periods of fishing and the use of the fishing methods in addition to the study of each type of these nets separately.